Exploring the Regulatory Mechanism of Hedysarum Multijugum Maxim.-Chuanxiong Rhizoma Compound on HIF-VEGF Pathway and Cerebral Ischemia-Reperfusion Injury’s Biological Network Based on Systematic Pharmacology - Yang, Kailin; Zeng, Liuting; Ge, Anqi; Chen, Yi; Wang, Shanshan; Zhu, Xiaofei; Ge, Jinwen (Frontiers in Pharmacology, 2021)
Background: Clinical research found that Hedysarum Multijugum Maxim.-Chuanxiong Rhizoma Compound (HCC) has definite curative effect on cerebral ischemic diseases, such as ischemic stroke and cerebral ischemia-reperfusion injury (CIR). However, its mechanism for treating cerebral ischemia is still not fully explained. Methods: The traditional Chinese medicine related database were utilized to obtain the components of HCC. The Pharmmapper were used to predict HCC’s potential targets. The CIR genes were obtained from Genecards and OMIM and the protein-protein interaction (PPI) data of HCC’s targets and IS genes were obtained from String database. After that, the DAVID platform was applied for Gene Ontology (GO) enrichment analysis and pathway enrichment analysis. Finally, a series of animal experiments were carried out to further explore the mechanism of HCC intervention in CIR. Results: The prediction results of systematic pharmacology showed that HCC can regulate CIR-related targets (such as AKT1, MAPK1, CASP3, EGFR), biological processes (such as angiogenesis, neuronal axonal injury, blood coagulation, calcium homeostasis) and signaling pathways (such as HIF-1, VEGF, Ras, FoxO signaling). The experiments showed that HCC can improve the neurological deficit score, decrease the volume of cerebral infarction and up-regulate the expression of HIF-1α / VEGF and VEGFR protein and mRNA (P<0.05). Conclusion: HCC may play a therapeutic role by regulating CIR-related targets, biological processes and signaling pathways found on this study.